Single-Center Experience With the Thoraflex™ Hybrid Prosthesis: Indications, Implantation Technique and Results - Wisniewski, Konrad; Motekallemi, Arash; Dell'Aquila, Angelo M.; Oberhuber, Alexander; Schaefers, Johannes F.; Ibrahim, Abdulhakim; Martens, Sven; Rukosujew, Andreas (Frontiers in Cardiovascular Medicine, 2022)
Objective The aim of this study was to evaluate the early and mid-term results after the frozen elephant trunk (FET) procedure for the treatment of complex arch and proximal descending aortic disease in a single-center institution. Methods From April 2015 to July 2021, 72 patients (25 women, 60.4 ± 10.3 years) underwent Thoraflex™ Hybrid implantation at our institution. The indications were thoracic aortic aneurysm (TAA) (n = 16, 22.2%), post-dissection aneurysm (n = 21, 29.2%), and acute aortic dissection (AAD) (n = 35, 48.6%). Antegrade cerebral perfusion under moderate hypothermia (28°C) was employed in all cases. Eighteen patients (25%) have already been operated due to heart or aortic disease. Results Overall in-hospital mortality was 12.5% (9 patients). Rates of permanent neurological dysfunction and spinal cord injury were 9.7 and 5.5%, respectively. The in-hospital mortality rate among patients operated on AAD, TAA, and post-dissection aneurysm were 8.6, 6.2, and 23.8%, respectively. At a mean follow-up of 26 ± 20 months, mortality was 9.7%. Furthermore, 23 patients (31.9%) required a subsequent procedure in distal aorta: endovascular stentgraft extension in 19 patients (26.4%) and open aortic surgery in 4 patients (5.5%). The mid-term survival of patients with type A aortic dissection was 97%. Conclusions Our experience with the Thoraflex Hybrid prosthesis demonstrates its surgical applicability for different types of aortic pathologies with promising outcomes during early and midterm follow-up. Our technique and perioperative management lead to comparable or even superior neurological outcomes and mortality in urgent cases considering other high-volume centers.